Copper and iron co-exchanged chabazite catalyst

By exchanging iron and copper ion on chabazeite and combining honeycomb substrate technology, the problem of catalyst activity decrease under hydrothermal conditions is solved, and efficient NOx conversion over a wide temperature range is achieved, meeting the requirements of government NOx regulations .

CN119215975APending Publication Date: 2024-12-31BASF CORPORATON
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411348035.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2016-02-03
Filing Date
2017-02-01
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing metal-promoted zeolite catalysts have decreased activity under strict hydrothermal conditions, especially the nitrogen oxide conversion rate in the low and high temperature ranges, and the hydrothermal stability is insufficient, making it difficult to meet the requirements of government NOx regulations.

Method used

Using a catalyst for iron and copper ion exchange on chabazeite (CHA), the catalyst is improved by contacting the chabazeite with copper and iron metal precursors, drying and calcining the catalyst in an active form, combining honeycomb substrate and support coating technology. Stability and activity of the catalyst.

Benefits of technology

It significantly improves the NOx conversion rate of the catalyst within the temperature range of 200-600℃, reduces the N2O level, extends the service life of the catalyst, and improves the low-temperature performance, meeting the requirements of government NOx regulations.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119215975A_ABST
    Figure CN119215975A_ABST
Patent Text Reader

Abstract

The present invention generally provides catalysts, catalytic articles, and catalyst systems comprising such catalytic articles. Specifically, the catalyst composition contains a zeolite having a chabazite (CHA) crystal structure that is ion-exchanged with iron and copper. Also provided are methods of making and using such catalyst compositions, as well as emission treatment systems comprising catalyst articles coated with catalyst compositions. A catalyst article in such an emission treatment system is useful for the catalytic reduction of nitrogen oxides present in an exhaust gas in the presence of a reducing agent.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of Chinese patent application 201780019587.2, the application date of which is February 1, 2017, and the name of the invention is “Copper and iron co-exchanged chabazite catalyst”. Technical Field

[0002] The present invention relates generally to the field of selective catalytic reduction catalysts, methods of making and using such catalysts for the selective reduction of nitrogen oxides. Background Art

[0003] Nitrogen oxides (NO x ) will cause air pollution over time. x , for example exhaust gases from internal combustion engines (such as cars and trucks), from combustion facilities (such as power stations heated with natural gas, oil or coal) and from nitric acid production plants.

[0004] Various treatment methods have been used to treat NO x A gas mixture is used to reduce atmospheric pollution. One type of treatment involves the catalytic reduction of nitrogen oxides. There are two methods: (1) a non-selective reduction method in which carbon monoxide, hydrogen or lower hydrocarbons are used as the reducing agent; and (2) a selective reduction method in which ammonia or an ammonia precursor is used as the reducing agent. In the selective reduction method, a high degree of nitrogen oxide removal can be achieved by using a small amount of reducing agent.

[0005] The selective reduction method is called the SCR (Selective Catalytic Reduction) method. The SCR method uses a reducing agent (such as ammonia) to catalytically reduce nitrogen oxides in the presence of atmospheric oxygen, resulting in the formation of mainly nitrogen and water vapor:

[0006] 4NO+4NH3+O2→4N2+6H2O (standard SCR reaction)

[0007] 2NO2+4NH3→3N2+6H2O (slow SCR reaction)

[0008] NO+NO2+NH3→2N2+3H2O (fast SCR reaction)

[0009] The catalyst used in the SCR process should ideally be able to maintain good catalytic activity under hydrothermal conditions over a wide range of operating temperature conditions, such as 200°C to 600°C or higher. SCR catalysts are often used under hydrothermal conditions, such as during the regeneration of soot filters, which are components of exhaust gas treatment systems for removing particulates. In the process of selective catalytic reduction of nitrogen oxides with reducing agents such as ammonia, urea or hydrocarbons in the presence of oxygen, molecular sieves such as zeolites have been used. Zeolites are crystalline materials with a very uniform pore diameter of about 3-10 angstroms, depending on the type of zeolite and the type and amount of cations contained in the zeolite lattice. Certain zeolites with 8-ring openings and two 6-ring auxiliary structural units, especially those with cage structures, have been used as SCR catalysts. A specific type of zeolite with these properties is chabazite (CHA), which is a small pore zeolite with an 8-membered ring opening (~3.8 angstroms) accessible through its three-dimensional porosity. The cage structure is obtained by connecting two 6-ring auxiliary structural units by 4 rings.

[0010] Metal-promoted zeolite catalysts are also often referred to as ion-exchanged zeolites or zeolites loaded with iron and / or copper, wherein iron-promoted and copper-promoted zeolite catalysts are well known for the selective catalytic reduction of nitrogen oxides with ammonia and can be prepared typically via metal ion exchange methods. For example, iron-promoted beta zeolite has been an effective commercial catalyst for the selective reduction of nitrogen oxides with ammonia. Unfortunately, it has been found that under severe hydrothermal conditions (e.g., during regeneration of soot filters at temperatures locally exceeding 700° C.), the activity of many metal-promoted zeolites begins to decline. This decline leads to dealumination of the zeolite, which in turn leads to a loss of metal-containing active centers within the zeolite.

[0011] Metal-promoted, especially copper-promoted, aluminosilicate zeolites having the CHA structure type have received considerable attention as catalysts for SCR of nitrogen oxides in lean-burn engines using nitrogen-containing reductants. These materials show activity over a wide temperature range and excellent hydrothermal durability, see U.S. Pat. No. 7,601,662. Prior to the discovery of the metal-promoted zeolites in U.S. Pat. No. 7,601,662, although many metal-promoted zeolites had been suggested in the patent and scientific literature for use as SCR catalysts, each of these materials suffered from one or both of the following disadvantages: (1) poor conversion of nitrogen oxides at low temperatures, such as 350° C. and lower; and (2) poor hydrothermal stability, which manifests itself in a significant decrease in catalytic activity when converting nitrogen oxides by SCR. The invention described in U.S. Pat. No. 7,601,662 addresses the unmet pressing need to provide a material that can convert nitrogen oxides at low temperatures and that maintains SCR catalytic activity after hydrothermal aging at temperatures exceeding 650° C.

[0012] Although the catalyst described in U.S. Pat. No. 7,601,662 shows excellent performance and can be used, for example, in SCR catalysis, there is still a need to improve performance over an extended and / or different temperature range. x One of the challenges of regulation is to improve the low temperature performance of prior art Cu-SSZ13 based SCR catalysts (e.g. Euro 6). Therefore, it would be beneficial to provide an SCR catalyst having improved low and high temperature performance and lower N2O levels compared to Cu-SSZ13 based SCR catalysts. Summary of the invention

[0013] The present invention generally provides catalysts, catalytic articles, and catalyst systems comprising such catalytic articles. In particular, such articles and systems contain an SCR catalyst comprising a combination of co-exchanged iron and copper on a chabazite (CHA) material.

[0014] In one aspect of the invention, the catalyst comprises a zeolite having a chabazite (CHA) crystal structure exchanged with iron and copper ions. These newly formed zeolite supports are often referred to as metal-promoted supports, in this case iron-promoted supports and / or copper-promoted supports. In addition, these metal ions are supported metal ions, such as supported iron and copper. Therefore, the terms "ion-exchanged" and "supported iron and / or copper" can be used interchangeably. In some embodiments, the pore size of the zeolite is about 3-5 angstroms. In another embodiment, the BET surface area of ​​the zeolite is at least about 400 m 2 / g.

[0015] In a particular embodiment, the CHA crystal structure of the catalyst is selected from aluminosilicate zeolites, borosilicates, gallosilicates, SAPO, ALPO, MeAPSO and MeAPO. For example, the CHA crystal structure can be further selected from SSZ-13, SSZ-62, natural chabazite, zeolite KG, Linde D, Linde R, LZ-218, LZ-235, LZ-236, ZK-14, SAPO-34, SAPO-4, SAPO-47, and ZYT-6.

[0016] In some embodiments, the CHA crystal structure of the catalyst is an aluminosilicate zeolite. The aluminosilicate zeolite has a silica to alumina ratio (SAR) of about 5-100, preferably about 10-40, and more preferably about 12-35.

[0017] In some embodiments, the catalyst has a D90 particle size of about 10-40 microns.

[0018] In other embodiments, the iron in the zeolite is present in an amount of about 0.01-6.0 wt % of the final metal ion exchanged zeolite composition, preferably about 0.5-4.5 wt % of the final metal ion exchanged zeolite composition, more preferably about 1-3.5 wt % of the final metal ion exchanged zeolite composition, calculated as iron oxide (Fe2O3). Similarly, the copper in the zeolite is present in an amount of about 0.01-6.0 wt % of the final metal ion exchanged zeolite composition, preferably about 0.5-5 wt % of the final metal ion exchanged zeolite composition, more preferably about 1-4 wt % of the final metal ion exchanged zeolite composition, calculated as copper oxide (CuO).

[0019] In another aspect, the present invention provides a method for preparing a CHA zeolite catalyst containing ion-exchanged iron and copper, comprising the steps of:

[0020] a) contacting chabazite (CHA) with a copper metal precursor and an iron metal precursor in a solution to form a solid CHA zeolite material containing the iron precursor and ion-exchanged copper;

[0021] b) drying the solid material to obtain a dry CHA zeolite catalyst containing iron and copper metal precursors; and

[0022] c) calcining the dry CHA zeolite catalyst containing the catalyst containing iron and copper metal precursors to convert the catalyst into an active form.

[0023] In some embodiments, the copper metal precursor described in this method is copper acetate. In another embodiment, the iron metal precursor described in this method is iron (III) nitrate. The chabazite (CHA) in this method is a Na-form chabazite and has been calcined prior to contact with the copper metal precursor and the iron metal precursor. In some embodiments, the copper metal precursor and the iron metal precursor in a solution are heated with the CHA zeolite at an elevated temperature. In some embodiments, the solution is an aqueous solution. In another embodiment, the drying of the solid material is carried out at an elevated temperature. In another embodiment, the CHA zeolite catalyst containing iron and copper metal precursors is calcined at a temperature of about 500-800°C.

[0024] Another aspect of the invention describes a catalyst article comprising a catalyst substrate having a plurality of channels for gas flow, each channel having a wall surface to which a catalytic coating containing a catalyst composition is adhered. In some embodiments, the catalyst substrate is a honeycomb. For example, the honeycomb substrate comprises a wall-flow filter substrate. In another example, the honeycomb substrate comprises a flow-through substrate. In some embodiments, the catalytic coating is at least about 1.0 g / in 3 In other embodiments, the catalytic coating is present on the substrate at a loading of at least about 2.0 g / in3 of the load is present on the substrate.

[0025] Another aspect of the present invention describes a method for reducing NO in exhaust gas. x The method comprises subjecting the exhaust gas to a catalyst at a temperature sufficient to reduce NO in the exhaust gas. x In some embodiments, the NO in the exhaust gas x The level is reduced to N2 at a temperature of 200-600°C. For example, NO in the exhaust gas x The level is reduced by at least 50% at 200°C. In another example, the NO in the exhaust gas x Levels are reduced by at least 70% at 600° C. In some embodiments, the catalyst article is a selective reduction catalyst (SCR).

[0026] Another aspect of the invention describes an exhaust treatment system comprising: a catalyst article located downstream of a combustion engine, and an injector for adding a reductant to the exhaust gas from the engine. In some embodiments, the engine is a diesel engine. In another embodiment, the exhaust treatment system further comprises a diesel oxidation catalyst. In another embodiment, the reductant in the exhaust treatment system comprises ammonia or an ammonia precursor.

[0027] The present invention includes, but is not limited to, the following embodiments.

[0028] Embodiment 1: A catalyst composition comprising a zeolite having a chabazite (CHA) crystal structure exchanged with iron and copper ions.

[0029] Embodiment 2: The catalyst composition of any preceding or subsequent embodiment, wherein the zeolite has a pore size of about 3-5 angstroms.

[0030] Embodiment 3: The catalyst composition of any preceding or subsequent embodiment, wherein the CHA crystal structure is selected from the group consisting of aluminosilicate zeolites, borosilicates, gallosilicates, SAPOs, ALPOs, MeAPSOs, and MeAPOs.

[0031] Embodiment 4: The catalyst composition of any of the preceding or subsequent embodiments, wherein the CHA crystal structure is an aluminosilicate zeolite having a silica to alumina ratio (SAR) of about 5-100.

[0032] Embodiment 5: The catalyst composition of any preceding or subsequent embodiment, wherein the aluminosilicate zeolite has a silica to alumina ratio (SAR) of about 10-40.

[0033] Embodiment 6: The catalyst composition of any of the preceding or subsequent embodiments, wherein the iron in the zeolite is present in an amount of about 0.01-6.0 weight percent of the final metal ion-exchanged zeolite, calculated as iron oxide (Fe2O3).

[0034] Embodiment 7: The catalyst composition of any of the preceding or subsequent embodiments, wherein the iron in the zeolite is present in an amount of about 0.5-4.5 weight percent of the final metal ion-exchanged zeolite, calculated as iron oxide (Fe2O3).

[0035] Embodiment 8: The catalyst composition of any of the preceding or subsequent embodiments, wherein the copper in the zeolite is present in an amount of about 0.01-6.0 wt % of the final metal ion exchanged zeolite, calculated as copper oxide (CuO).

[0036] Embodiment 9: The catalyst composition of any of the preceding or subsequent embodiments, wherein the copper in the zeolite is present in an amount of about 0.5-5 wt % of the final metal ion exchanged zeolite, calculated as copper oxide (CuO).

[0037] Embodiment 10: The catalyst composition of any of the preceding or subsequent embodiments, wherein the zeolite has a 2 / g of BET surface area.

[0038] Embodiment 11: The catalyst composition of any of the preceding or subsequent embodiments, having a D of about 10-40 microns. 90 Particle size.

[0039] Embodiment 12: A method for preparing a CHA zeolite catalyst containing iron and copper, comprising: a. contacting chabazite (CHA) with a copper metal precursor and an iron metal precursor in a solution to form a solid CHA zeolite material containing iron and copper; b. drying the solid material to obtain a CHA zeolite catalyst containing iron and copper metal precursors; and c. calcining the CHA zeolite catalyst containing the catalyst containing iron and copper metal precursors to convert the catalyst into an active form.

[0040] Embodiment 13: The method of any preceding or subsequent embodiment, wherein the copper metal precursor is copper acetate or copper nitrate salt.

[0041] Embodiment 14: The method of any preceding or subsequent embodiment, wherein the iron metal precursor is an iron (III) nitrate or iron (II) acetate salt.

[0042] Embodiment 15: The method of any preceding or subsequent embodiment, wherein the chabazite (CHA) is Na-form chabazite and has been calcined prior to contacting with the copper metal precursor and the iron metal precursor.

[0043] Embodiment 16: The method of any preceding or subsequent embodiment, further comprising heating the copper metal precursor and the iron metal precursor in the solvent with the CHA zeolite at an elevated temperature.

[0044] Embodiment 17: The method of any preceding or subsequent embodiment, wherein the CHA zeolite catalyst containing the catalyst containing iron and copper metal precursors is calcined at a temperature of about 500-800°C.

[0045] Embodiment 18: The method of any preceding or subsequent embodiment, wherein the solution is an aqueous solution.

[0046] Embodiment 19. A catalyst article comprising a catalyst substrate having a plurality of channels for gas flow, each channel having a wall surface adhered to a catalytic coating, the catalytic coating comprising a catalyst composition according to any of the preceding or subsequent embodiments.

[0047] Embodiment 20: The catalyst article of any preceding or subsequent embodiment, wherein the catalyst substrate is a honeycomb substrate in the form of a wall-flow filtration substrate or a flow-through substrate.

[0048] Embodiment 21: The catalyst article of any of the preceding or subsequent embodiments, wherein the catalytic coating is at least about 1.0 g / in 3 of the load is present on the substrate.

[0049] Embodiment 22: A method for reducing NO in exhaust gas x The method comprises subjecting the exhaust gas to a catalyst at a level sufficient to reduce NO in the exhaust gas. x The method comprises contacting the catalyst with the catalyst composition according to any one of the preceding or subsequent embodiments at a temperature and time level.

[0050] Embodiment 23: The method of any of the preceding or subsequent embodiments, wherein the NO in the exhaust gas x It is reduced to N2 at a temperature of about 200-600°C.

[0051] Embodiment 24: The method of any of the preceding or subsequent embodiments, wherein the NO in the exhaust gas x The level decreases by at least 50% at 200°C.

[0052] Embodiment 25: The method of any of the preceding or subsequent embodiments, wherein the NO in the exhaust gas x The level decreases by at least 70% at 600°C.

[0053] Embodiment 26: An emission treatment system for treating an exhaust stream, the emission treatment system comprising: (i) an engine that generates the exhaust stream; (ii) a catalyst article according to any of the preceding or subsequent embodiments, located downstream of the engine and in fluid communication with the exhaust stream, and for reducing NO in the exhaust stream. x to form a treated exhaust stream; and (iii) an injector for adding a reductant to the exhaust stream to promote the conversion of NO to the exhaust stream when the exhaust stream is exposed to the catalyst article. x Reduced to N2 and water.

[0054] Embodiment 27: The emission treatment system of any preceding or subsequent embodiment, wherein the engine is a diesel engine.

[0055] Embodiment 28: The emission treatment system of any preceding or subsequent embodiment, further comprising a diesel oxidation catalyst.

[0056] Embodiment 29: The emission treatment system of any preceding or subsequent embodiment, wherein the reductant contains ammonia or an ammonia precursor.

[0057] These and other features, aspects and advantages of the present invention will be apparent from the following detailed description and the accompanying drawings, which will be briefly described below. The present invention includes any combination of two, three, four or more of the above-described embodiments, as well as any combination of two, three, four or more features or elements described in the present invention, regardless of whether these features or elements are explicitly combined in a specific embodiment. The present invention should be understood as a whole, so that any individual feature or element of the present invention should be considered combinable in any various aspects and embodiments, unless otherwise explicitly stated. Other aspects and advantages of the present invention will be apparent from the following. BRIEF DESCRIPTION OF THE DRAWINGS

[0058] In order to facilitate understanding of the embodiments of the present invention, reference may be made to the following drawings, which are not necessarily drawn to scale, wherein each mark represents a component in an exemplary embodiment of the present invention. These drawings are merely exemplary and do not limit the present invention.

[0059] Figure 1 is a perspective view of a honeycomb-type substrate carrier that may contain a washcoat composition of a catalytic article of the present invention, i.e., a selective reduction catalyst (SCR);

[0060] Figure 2 is relative to Figure 1 A magnified partial cross-sectional view taken along the flow-through substrate showing the monolith Figure 1 The plane parallel to the end surface of the substrate carrier is obtained and displayed Figure 1 An enlarged view of the multiple airflow paths shown in FIG.

[0061] Figure 3 is relative to Figure 1 An intercept view of an enlarged section, where Figure 1 The honeycomb type substrate carrier in the embodiment represents a wall flow type filtration substrate monolith; and

[0062] Figure 4 A schematic diagram is shown of one embodiment of an emissions treatment system in which the SCR of the present invention is used. DETAILED DESCRIPTION

[0063] The present invention will be described in more detail below. However, the present invention can be embodied in many different forms and should not be limited to the embodiments described herein; rather, these embodiments are provided to fully complete the present invention and enable those skilled in the art to fully understand the scope of the present invention. Unless otherwise indicated, the singular forms "a", "an" and "the" used in the specification and claims include plural forms.

[0064] The present invention provides a selective reduction catalyst (SRC) composition suitable for gaseous NO x At least partial oxidation of emissions and reduction of NO. The SRC composition comprises at least two metal oxide components ion-exchanged on a porous refractory oxide support, which can provide NO x Effects on Conversion Activity. SRC compositions can be prepared using a metal ion exchange method, rather than an incipient wetness impregnation technique, to obtain a catalyst composition that can then be coated onto a catalyst substrate using a support coating technique, as described in detail below.

[0065] Ion exchange is a common method for exchanging ions resident in a porous support with an external metal ion of interest. For example, a zeolite with sodium ions resident in the pores can be exchanged with different ions to form a porous support for ion exchange. This is achieved by preparing a slurry of the porous support, i.e., the zeolite, in a solution containing the external metal ions to be exchanged. Heating can be optional during this method. The external metal ions can diffuse into the pores of the support and exchange with the resident ions, i.e., sodium, to form a porous support for metal ion exchange.

[0066] However, unlike the ion exchange method, the incipient wetness impregnation technique, also known as capillary impregnation or dry impregnation, is commonly used to synthesize multiphase materials, i.e., catalysts, without the need for any resident ions in the raw materials. Typically, the metal precursor is dissolved in an aqueous or organic solution, and the metal-containing solution is then added to a catalyst support, i.e., a zeolite, which contains a pore volume equal to the volume of solution added. Capillary action draws the solution into the pores of the support. The addition of an excess of solution compared to the support pore volume causes the solution transport to change from a capillary action process to a diffusion process, which is significantly slower. The catalyst can then be dried and calcined to drive off the volatile components in the solution so that the metal is deposited on the catalyst surface. The maximum load is limited by the solubility of the precursor in the solution. The concentration distribution of the impregnated material depends on the mass transfer conditions in the pores during impregnation and drying.

[0067] In this application, the following terms shall have the corresponding meanings set out below.

[0068] As used herein, the term "selective catalytic reduction" (SCR) refers to a catalytic process that uses a nitrogen-containing reductant (eg, ammonia, urea, etc.) to reduce nitrogen oxides to dinitrogen (N2).

[0069] The term "catalyst" or "catalyst composition" as used herein refers to a material that promotes a reaction. The term "catalyst system" as used herein refers to a combination of two or more catalysts, such as a combination of a first SCR catalyst and a second SCR catalyst. The catalyst system may be in the form of a washcoat in which two SCR catalysts are mixed together.

[0070] The terms "upstream" and "downstream" as used herein refer to the respective directions of flow of the engine exhaust stream from the engine to the exhaust conduit, wherein the engine is in an upstream position and the exhaust conduit and any articles used to reduce pollution, such as filters and catalysts, are downstream of the engine.

[0071] The term "stream" as used herein refers broadly to any combination of flowing gases, which may contain solid or liquid particulate matter. The term "gaseous stream" or "exhaust stream" refers to a stream of gaseous components, such as the exhaust of a lean-burn engine, which may contain entrained non-gaseous components such as liquid droplets, solid particles, etc. The exhaust stream of a lean-burn engine also typically contains combustion products, products of incomplete combustion, nitrogen oxides, combustible and / or carbonaceous particulate matter (soot), and unreacted oxygen and nitrogen.

[0072] The term "substrate" as used herein refers to a monolithic material on which a catalyst composition is disposed, which is typically in the form of a washcoat comprising a plurality of particles containing the catalytic composition. The washcoat is formed by preparing a slurry of particles having a specific solid content (e.g., 30-90 wt%) in a liquid medium, which is then coated onto a substrate and dried to provide a washcoat.

[0073] The term "washcoat" as used herein has its conventional meaning in the art and is a thin, adherent coating of catalytic or other material applied to a substrate material, such as a honeycomb-type substrate element, which is sufficiently porous to permit the passage of the gas stream being processed.

[0074] As used herein, the term "catalytic article" refers to an element used to promote a desired reaction. For example, a catalytic article may comprise a washcoat layer comprising a catalytic composition on a substrate.

[0075] The term "reduce" (verb) means a decrease in quantity, and "reduce" (noun) means a decrease in quantity caused by any means.

[0076] The term "impregnated" or "impregnation" as used herein means that the catalytic material penetrates into the porous structure of the support material.

[0077] The term "pseudocrystalline" is used here to denote a material that appears crystalline even under a microscope, but which does not have a true crystalline diffraction pattern.

[0078] Catalyst composition

[0079] The SRC composition comprises a combination of copper and iron ion-exchanged on a chabazite (CHA) carrier. In a particular embodiment, the combination of copper and iron ion-exchanged on a chabazite (CHA) carrier is expressed as a weight ratio of the corresponding metal oxides. In some embodiments, the weight ratio between copper oxide and iron oxide is in the range of about 1:10 to 10:1, more typically about 1:3 to 3:1. The concentration of the copper and iron components can vary, but is typically about 0.1-12 wt % (e.g., about 6 -8 wt % based on the final metal ion exchange zeolite carrier composition) based on the total weight of the zeolite carrier material, calculated as metal oxides. In some embodiments, the amount of iron present in the zeolite is about 0.01-6.0 wt % of the final metal ion exchange zeolite composition, preferably about 0.5-4.5 wt % of the final metal ion exchange zeolite composition, more preferably about 1-3.5 wt % of the final metal ion exchange zeolite composition, calculated as iron oxide (Fe2O3). In another embodiment, the copper in the zeolite is present in an amount of about 0.01-6.0 weight percent of the final metal ion exchange zeolite composition, preferably about 0.5-5.0 weight percent of the final metal ion exchange zeolite composition, and more preferably about 1-4 weight percent of the final metal ion exchange zeolite composition, calculated as copper oxide (CuO). These newly formed zeolite supports are generally referred to as metal-promoted supports, in this case iron-promoted supports and / or copper-promoted supports. In addition, these metal ions are supported metal ions, such as supported iron and copper. Therefore, the terms "ion exchanged" and "supported iron and / or copper" can be used interchangeably.

[0080] The zeolite of the present invention is a zeolite with a chabazite (CHA) crystal structure, which is selected from aluminosilicate zeolites, borosilicates, gallosilicates, SAPOs, ALPOs, MeAPSOs and MeAPOs. In some embodiments, the CHA crystal structure is an aluminosilicate zeolite. Aluminosilicate zeolites can have a crystalline or pseudocrystalline structure and can include a framework metal different from aluminum (i.e., metal substituted), such as silicoaluminophosphates (SAPOs). Natural and synthetic zeolites can also be used, but synthetic zeolites are preferred because these zeolites have a more uniform silica-alumina ratio (SAR), crystallite size and crystallite morphology, and have less and less concentrated impurities (e.g., alkaline earth metals). Specific zeolites having a CHA structure that can be used in the present invention include, but are not limited to, SSZ-13, SSZ-62, natural chabazite, zeolite KG, Linde D, Linde R, LZ-218, LZ-235, LZ-236, ZK-14, SAPO-34, SAPO-4, SAPO-47, and ZYT-6.

[0081] Zeolites as crystalline materials have fairly uniform pore sizes, ranging from about 3-10 angstroms in diameter, depending on the type of zeolite and the type and amount of cations contained within the zeolite lattice. In one embodiment, CHA zeolite has pore sizes of about 3-5 angstroms.

[0082] Zeolites are typically present as highly crystalline materials that are at least about 75% crystalline, at least about 80% crystalline, at least about 85% crystalline, at least about 90% crystalline, at least about 95% crystalline, at least about 98% crystalline, at least about 99% crystalline, or at least about 99.5% crystalline. Zeolite synthesis methods vary depending on the type of molecular sieve material structure, but are typically synthesized using a structure directing agent (SDA), sometimes referred to as a template (or organotemplate), along with a source of silica and alumina. The SDA can be in the form of an organic cation, i.e., tetraethylammonium hydroxide (TEAOH), or an inorganic cation, i.e., Na + or K + . During crystallization, tetrahedral units are ordered around the SDA to form the desired framework, and the SDA is typically embedded within the pore structure of the zeolite crystal. In one or more embodiments, crystallization of the first and second molecular sieves can be achieved by adding a structure directing agent / template, a crystal nucleus, or an element. Exemplary methods for preparing zeolites can be found in U.S. Patent Nos. 8,293,198 to Beutel et al.; 8,715,618 to Trukhan et al.; 9,162,218 to Bull et al.; and 8,883,119 to Bull et al., the contents of which are incorporated herein by reference in their entirety.

[0083] Zeolites typically contain a molar ratio (SAR) of silica to alumina of 2 or greater. However, the silica to alumina ratio of the molecular sieve component can vary over a wide range. In one or more embodiments, the alumina molar ratio (SAR) is in the range of up to 300, including about 5-250; about 10-100; about 15-75; and about 20-50.

[0084] Typically, molecular sieves such as zeolites are defined as aluminosilicates having an open three-dimensional framework structure consisting of corner-sharing TO4 tetrahedra, where T is Al or Si. The cations used to balance the charge of the anionic framework are loosely bound to the framework oxygens, and the remaining pore volume is filled with water molecules. Non-framework cations are generally exchangeable, and the water molecules are removable.

[0085] Zeolite support materials typically exhibit BET surface areas in excess of 60 m 2 / g, usually up to 200m 2 / g or more. "BET surface area" has the conventional meaning with respect to the Brunauer, Emmett, Teller method for measuring surface area by N2 adsorption. In one or more embodiments, the BET surface area is at least about 200 m 2 / g, or at least about 400m 2 / g, or at least about 600m 2 / g.

[0086] The particle size of the zeolite can vary. Typically, the particle size of CHA zeolite can be characterized by a D90 particle size of about 10-40 microns, preferably about 10-30 microns, and more preferably 10-20 microns. D90 is defined as the particle size at which 90% of the particles have a finer particle size.

[0087] In one embodiment, the Cu / Fe co-exchanged chabazite catalyst can be accomplished by a one-step direct co-exchange of calcined Na-form chabazite. The Na-form zeolite should preferably be calcined at the lowest practical temperature (≤540°C) prior to exchange to remove or minimize the formation of extra-framework aluminum species and / or distorted aluminum sites. The co-exchange can be performed at 60°C for 1 hour using copper acetate and iron (III) nitrate as metal precursors. The copper acetate can be added first, followed by iron (III) nitrate nonahydrate. Although Fe(III) is typically exchanged at 100%, the appropriate amount of copper acetate can be predetermined using an ion exchange isotherm. After the exchange is completed, the sample is filtered using a Buchner funnel and washed to a conductivity of <200 μmhos, then dried in a drying oven at 85°C. The copper and iron contents are analyzed using ICP and are reported as oxides on a volatile-free basis (see Table 1 in Example 1).

[0088] Substrate

[0089] According to one or more embodiments, the substrate for the catalyst article composition (i.e., SRC catalyst composition) can be composed of any material commonly used to prepare automotive catalysts, typically comprising a metal or ceramic honeycomb structure. The substrate typically provides a plurality of wall surfaces on which the catalyst article (i.e., SRC catalyst) washcoat composition is applied and adhered, thereby serving as a support for the catalyst composition.

[0090] Exemplary metal substrates include heat-resistant metals and metal alloys, such as titanium and stainless steel, and other alloys in which iron is a significant or major component. Such alloys may contain one or more of nickel, chromium and / or aluminum, and the total amount of these metals may advantageously comprise at least 15% by weight of the alloy, such as 10-25% by weight of chromium, 3-8% by weight of aluminum, and up to 20% by weight of nickel. The alloy may also contain small or trace amounts of one or more other metals, such as manganese, copper, vanadium, titanium, etc. The surface or metal carrier may be oxidized at high temperatures, such as 1000° C. or higher, thereby forming an oxide layer on the substrate surface, which improves the corrosion resistance of the alloy and promotes adhesion of the carrier coating to the metal surface.

[0091] The ceramic material used to form the substrate may include any suitable refractory material, such as cordierite, mullite, cordierite-alpha alumina, silicon nitride, zircon mullite, spodumene, alumina-silica magnesia, zirconium silicate, sillimanite, magnesium silicate, zircon, feldspar, alpha-alumina, aluminosilicate, and the like.

[0092] Any suitable substrate may be used, such as a monolithic flow-through substrate having a plurality of fine parallel gas flow channels extending from the inlet end face of the substrate to the outlet end face, such that the channels are open to the fluid flowing therethrough. Those channels that are substantially in a straight line path from their inlet to the outlet are defined by walls, and the catalytic material is coated on the walls as a washcoat so that the gas flowing through the channels contacts the catalytic material. The flow channels of the monolithic substrate are thin-walled channels that may have any suitable cross-sectional shape, such as trapezoidal, rectangular, square, sinusoidal, hexagonal, elliptical, circular, and the like. These structures may contain about 60-1200 or more gas inlet openings (i.e., "openings") per square inch of cross section (cpsi), more typically about 300-600 cpsi. The wall thickness of the flow-through substrate may vary, typically in the range of 0.002-0.1 inches. Representative commercially available flow-through substrates are cordierite substrates having 400 cpsi and a wall thickness of 6 mils, or 600 cpsi and a wall thickness of 4 mils. It should be understood, however, that the present invention is not limited to a particular substrate type, material, or geometry.

[0093] In other embodiments, the substrate can be a wall-flow substrate, wherein each channel is closed with a non-porous plug at one end of the substrate body, and the other channels are closed at the opposite end face. This requires gas to flow through the porous wall of the wall-flow substrate to reach the outlet. This monolithic substrate can have up to about 700 or more cpsi, for example, about 100-400 cpsi, more usually about 200-300 cpsi. The cross-sectional shape of these openings can be changed as described above. The wall-flow substrate generally has a wall thickness of 0.002-0.1 inches. Representative commercially available wall-flow substrates are formed by porous cordierite, for example, with 200 cpsi and a wall thickness of 10 mils, or with 300 cpsi and a wall thickness of 8 mils, and a wall porosity of 45-65%. Other ceramic substrates can also be used as wall-flow filtration substrates, such as aluminum titanate, silicon carbide and silicon nitride. However, it should be understood that the present invention is not limited to specific substrate types, materials or geometries. It should be noted that when the substrate is a wall-flow substrate, in addition to being on the wall surface, the catalyst article (ie, SCR catalyst) composition may also penetrate into the pore structure of the porous wall (ie, partially or completely enclose the open pore openings).

[0094] Figure 1 and 2 An exemplary substrate 2 is shown which is in the form of a flow-through substrate coated with a washcoat composition of the present invention. Figure 1 The exemplary substrate 2 is cylindrical, having a cylindrical outer surface 4, an upstream end surface 6, and a corresponding downstream end surface 8 identical to the end surface 6. A plurality of fine parallel gas flow channels 10 are provided in the substrate 2. Figure 2 The flow channel 10 is formed by the wall 12 and extends from the upstream end face 6 to the downstream end face 8 in the carrier 2. The channel 10 is unobstructed, thereby allowing a fluid, such as an airflow, to flow in the carrier 2 through the airflow channel 10 in the longitudinal direction. Figure 2 It is apparent that the dimensions and configuration of the walls 12 provide the gas flow channel 10 with a substantially regular polygonal shape. As shown, the washcoat composition may be applied as a plurality of separate layers if desired. In the illustrated embodiment, the washcoat layer consists of a separate bottom washcoat layer 14 adhered to the walls 12 of the carrier element and a separate second top washcoat layer 16 applied over the bottom washcoat layer 14. The present invention may be implemented with one or more (e.g., 2, 3, or 4) washcoats and is not limited to the two-layer embodiment described.

[0095] or, Figure 1 and 3 An exemplary substrate 2 can be shown which is in the form of a wall flow filter substrate coated with a washcoat composition of the present invention. Figure 3, the exemplary substrate 2 has a plurality of passages 52. These passages are wrapped in a tubular manner by the inner wall 53 of the filtering substrate. The substrate has an inlet end 54 and an outlet end 56. Other passages are plugged by an inlet plug 58 at the inlet end and by an outlet plug 60 at the outlet end, thereby forming an opposite checkerboard pattern at the inlet 54 and the outlet 56. The gas stream 62 enters through the unplugged channel inlet 64, is blocked by the outlet plug 60 and diffuses to the outlet side 66 via the channel wall 53 (which is porous). Due to the inlet plug 58, the gas cannot return to the inlet side of the wall. The porous wall flow filter used in the present invention is catalyzed by one or more catalytic materials on the wall of the element or contained therein. These catalytic materials can be present on only the inlet side of the element wall, on only the outlet side, on both the inlet and outlet sides, or the wall itself can be composed of catalytic materials in whole or in part. The present invention includes one or more layers of catalytic materials used on the inlet and / or outlet walls of the element.

[0096] When describing the amount of catalytic metal component or other component of a washcoat or composition, it is convenient to use the unit of weight of the component per unit volume of the catalyst substrate. Thus, the units used are grams per cubic inch ("g / in 3 ”) and grams per cubic foot (“g / ft 3 ”) is used to express the weight of the component based on the volume of the substrate, wherein the volume of the substrate includes the volume of the interstitial space of the substrate. Other weight / volume units, such as g / L, are sometimes used. The total loading of the composition (i.e., two ion-exchanged metals on a zeolite support material) on a catalyst substrate such as a monolithic flow-through substrate is typically about 0.5-6 g / in 3 , more usually about 1-5 g / in 3 It should be noted that these weights per unit volume are generally calculated by weighing the catalyst substrate before and after treatment with the catalyst washcoat composition, and because this treatment process involves drying and calcining the catalyst substrate at elevated temperatures, these weights represent a substantially solvent-free catalyst washcoat since substantially all of the water in the washcoat slurry has been removed.

[0097] Method for preparing catalyst composition

[0098] The preparation method of metal ion exchange zeolite material generally comprises: a method of ion exchanging a zeolite support material in the form of particles with a metal precursor solution. Multiple metal precursors (e.g., copper and iron) are ion exchanged simultaneously or separately, using the same external solution for ion exchange, and ion exchange is performed on the same support particles. For example, CHA zeolite particles are used as support particles.

[0099] When the ion exchange isotherm of the first metal precursor must be determined before adding the second metal precursor, multiple metal precursors are added separately. The ion exchange isotherm describes the concentration of the first metal ion precursor as its concentration in the external solution changes at any given temperature and pressure. Complete co-exchange between the first metal precursor ions and the ions resident in the support material is when the concentration of the first metal precursor is an effective concentration in the external solution to promote the completion of this ion exchange at any given temperature and pressure. After the co-exchange of the ions of the first metal precursor is completed, the second metal precursor is added to the same external solution to allow the co-exchange of the ions of the second metal precursor.

[0100] The support particles are typically dry enough to absorb substantially all of the solution to form a wet solid. For example, the Na form of chabazite can be calcined to provide a dry Na-chabazite prior to contacting with the precursor metal. An aqueous solution of a water-soluble compound or a complex of a metal precursor is typically used, such as a nitrate or acetate of the metal precursor, specific examples of which include copper (II) nitrate, copper (II) acetate, iron (II) acetate, iron (III) nitrate, and iron (III) acetate.

[0101] After treating the support particles with the solution of the metal precursor, the particles are dried, for example by heat treating the particles at an elevated temperature (e.g., 100-150° C.) for a certain time (e.g., 1-3 hours), and then calcined to convert the metal component to an oxide form having a higher catalytic activity. An exemplary calcination method involves heat treatment at a temperature of about 500-800° C. in air for about 1-3 hours. The above method can be repeated as needed to achieve the desired level of impregnation with the metal precursor. The resulting material can be stored as a dry powder or in the form of a slurry.

[0102] Method for coating a substrate

[0103] The above catalyst composition is in the form of support particles containing a combination of metal components to be ion-exchanged therein, and the catalyst composition is mixed with water to form a slurry for coating a catalyst substrate, such as a honeycomb substrate. In addition to the catalyst particles, the slurry may optionally contain alumina as a binder, a water-soluble or water-dispersible stabilizer (such as barium acetate), a promoter (such as lanthanum nitrate), an associative thickener, and / or a surfactant (including anionic, cationic, nonionic or amphiphilic surfactants).

[0104] When present, the amount of alumina binder is generally about 0.05-1 g / in 3 The alumina binder may be, for example, boehmite, gamma-alumina or delta / theta-alumina.

[0105] The slurry may be ground to improve the mixing of the particles and the formation of a homogeneous material. The grinding may be carried out in a ball mill, a continuous mill or other similar equipment, and the solid content of the slurry may be, for example, about 20-60% by weight, more particularly about 30-40% by weight. In one embodiment, the ground slurry has a D90 particle size of about 10-40 microns, preferably 10-30 microns, more preferably about 10-15 microns. D90 is defined as the particle size at which about 90% of the particles have a finer particle size.

[0106] The slurry is then coated onto the catalyst substrate using washcoating techniques known in the art. In one embodiment, the catalyst substrate is dipped into the slurry one or more times, or coated with the slurry. The coated substrate is then dried at an elevated temperature (e.g., about 100-150° C.) for a certain time (e.g., 1-3 hours) and then calcined by heating, such as heating at about 400-600° C. for a time typically from about 10 minutes to about 3 hours. After drying and calcining, the final washcoat layer can be considered to be substantially solvent-free.

[0107] After calcination, the catalyst loading can be determined by calculating the difference between the weight of the coated substrate and the weight of the uncoated substrate. It will be apparent to those skilled in the art that catalyst loading can be modified by changing the slurry rheology. In addition, the coating / drying / calcining process for producing the washcoat can be repeated as needed to achieve the desired loading level or thickness of the coating, which means that more than one washcoat can be applied.

[0108] The catalyst composition may be applied as a single layer or multiple layers. In one embodiment, the catalyst is applied as a single layer (e.g. Figure 2 In another embodiment, the catalyst composition is applied as multiple layers (e.g. Figure 2 Layers 14 and 16 in FIG.

[0109] Emission treatment system

[0110] The present invention also provides an emission treatment system in which the SRC catalyst composition (i.e., catalytic product) of the present invention is introduced. The SRC catalyst composition of the present invention is generally used in an integrated emission treatment system comprising one or more additional components for treating exhaust emissions, such as exhaust emissions from a diesel engine. For example, the emission treatment system may also include a catalytic soot filter (CSF) component and / or a selective diesel oxidation (DOC) catalytic product. The SRC catalyst of the present invention is generally located upstream or downstream of the soot filter, and downstream of the diesel oxidation catalyst component, but the relative arrangement of the various components of the emission treatment system may vary. The emission treatment system also includes other components, such as a reductant injector for an ammonia precursor, and may optionally include any additional particle filter components, NO x Storage and / or Capture Components The above listed components are merely illustrative and should not be considered to limit the scope of the present invention.

[0111] The CSF may contain a substrate coated with a washcoat containing one or more catalysts for burning captured soot and / or oxidizing exhaust stream emissions. In general, the soot combustion catalyst may be any known catalyst for burning soot. For example, the CSF may be catalyzed with one or more high surface area refractory oxides (e.g., alumina or zirconia) and / or oxidation catalysts (e.g., ceria-zirconia) for burning unburned hydrocarbons and to some extent particulate matter. The soot combustion catalyst may be an oxidation catalyst containing one or more precious metal catalysts (e.g., platinum, palladium, and / or rhodium). In some embodiments, the CSF may contain a substrate coated with a washcoat containing one or more catalysts for reducing NO in exhaust stream emissions. x For example, CSF can be catalyzed with one or more selective reduction catalysts to convert NO in the exhaust stream. x , additionally containing one or more layers containing one or more catalysts for combusting captured soot and / or for oxidizing exhaust stream emissions.

[0112] Figure 4 An exemplary emission treatment system is shown, wherein a schematic diagram of an emission treatment system 32 is depicted. As shown, an exhaust stream containing gaseous pollutants and particulate matter is sent from an engine 34 via an exhaust conduit 36 ​​to a diesel oxidation catalyst (DOC) 38, to a catalyzed soot filter (CSF), and then to a selective reduction catalyst (SRC), wherein the SRC is coated with a washcoat composition of the present invention. In the DOC 38, unburned gaseous and non-volatile hydrocarbons (i.e., SOF) and carbon monoxide are mostly burned to form carbon dioxide and water. In addition, NO x A certain proportion of NO in the composition can be oxidized to NO2 in the DOC.

[0113] The exhaust stream is then sent via exhaust conduit 40 to a catalyzed soot filter (CSF) 42, which is used to capture particulate matter present in the exhaust stream. CSF 42 is optionally catalyzed to achieve passive or active soot regeneration. CSF 42 may optionally include an SRC composition, which is used to convert NO present in the exhaust gas. x .

[0114] After removal of the particulate matter, the exhaust stream is sent downstream through the CSF 42 to the selective catalytic reduction (SCR) component 46 of the present invention via the exhaust conduit 44 for further treatment and / or conversion of NO x The exhaust gas is passed through the SCR component 46 at a flow rate that allows the catalyst composition to adequately reduce NO in the exhaust gas at a given temperature. x When CSF 42 already contains an SRC composition, an SCR component 46 may optionally be included in the exhaust treatment system. An injector 50 for introducing a nitrogenous reductant into the exhaust stream is located upstream of SRC 46. In some embodiments, injector 50 may also be introduced upstream of CSF 42, provided that CSF 42 contains an SCR composition. The operation of introducing a nitrogenous reductant into the gas exhaust stream can promote NO when the gas is exposed to the catalyst composition. x Reduced to N2 and water.

[0115] Regarding this SCR method, a method for reducing NO in exhaust gas is provided. x The method comprises exposing the exhaust gas to a catalyst composition as described herein and optionally in the presence of a reducing agent in an amount sufficient to catalytically reduce NO x time and temperature contact, thereby reducing NO in the exhaust x In certain embodiments, the temperature range is about 200-600°C. For example, at a temperature of 200°C, the catalyst composition of the present invention reduces NO in the exhaust gas to x Similarly, at a temperature of 600°C, the catalyst composition of the present invention reduces the NO in the exhaust gas by at least about 50%. x Levels were reduced by at least about 70%. x The amount of reduction depends on the contact time of the exhaust gas stream with the catalyst, and therefore on the space velocity. There is no particular limitation on the contact time and space velocity in the present invention. However, the catalyst composition of the present invention has been shown to improve NO reduction compared to commercial control SCR catalysts. x Thus, the catalyst composition can operate well even at high space velocities, which may be desirable in certain applications.

[0116] Nitrogen-containing reducing agents can be used to treat NO xIn general, the reductant used in the SCR method refers to a reductant that can promote the reduction of NO in the exhaust gas. x Examples of such reducing agents include ammonia, hydrazine, or any suitable ammonia precursor, such as urea ((NH2)2CO), ammonium carbonate, ammonium carbamate, ammonium bicarbonate, or ammonium formate. In one embodiment, the nitrogen-containing reducing agent is added using a reducing agent injector, which adds the ammonia precursor to the exhaust stream upstream of SRC 46. The presence of ammonia or an ammonia precursor in the exhaust stream can promote the conversion of NO when the gas is exposed to the catalyst composition. x Reduced to N2 and water.

[0117] Example

[0118] Various aspects of the present invention are more fully illustrated by the following examples, which are intended to illustrate specific aspects of the present invention and are not intended to limit the scope of the present invention.

[0119] The following examples relate to Cu / Fe co-exchanged chabazite (CHA) catalysts for diesel NO x In order to reduce the application, these examples provide a method for preparation and show that the 3 Improved high temperature SCR performance was obtained on coated cores at nominal load (dry weight gain).

[0120] Example 1: Preparation of SCR catalyst

[0121] The dry Na-chabazite is prepared by calcining Na-chabazite at the lowest practical temperature (≤ 540°C) to remove or minimize the formation of extra-framework aluminum species and / or distorted aluminum sites to provide a dry calcined Na-chabazite.

[0122] The calcined Na-chabazite was placed in a reaction vessel, and deionized water and cupric acetate were then added while mixing. Finally, iron (III) nitrate nonahydrate was added. The reaction mixture was heated at 60°C for about 1 hour. The exchange of iron (III) nitrate with the sodium ions present in the zeolite was carried out at 100% conversion. The amount of cupric acetate was predetermined using an ion exchange isotherm. After the ion exchange was completed, the sample was filtered and washed with a Buchner funnel to achieve a conductivity of <200 μmhos and then dried in a drying oven at 85°C. The copper and iron content of the zeolite material was analyzed using ICP and reported as oxides on a volatile-free basis (see Table 1).

[0123] For the preparation of Catalyst 3 in Table 1, the following procedure was used, including the amounts of the reagents used:

[0124] 110 g of calcined Na-chabazite was placed in a reaction vessel, followed by the addition of deionized water and cupric acetate (10.4 g) while mixing. Finally, iron (III) nitrate nonahydrate (2.75 g) was added. The reaction mixture was heated at 60°C for about 1 hour. The reaction mixture was allowed to cool and then filtered using a Buchner funnel connected to a 4 L flask. The collected solids were washed with deionized water (about 5.5 L) until the catalyst reached <200 μmhos. The collected solid sample was dried in a drying oven at 85°C overnight to obtain 1-2 g of dried catalyst sample 3. When used for chemical analysis, the sample contained CuO (VF), Fe2O3 (VF), wherein CuO = 3.1% and Fe2O3 = 0.46% volatile-free (VF).

[0125] The co-exchanged sample of the zeolite material is then coated on the core. A slurry is prepared by mixing Cu / Fe co-exchanged chabazite (1 part, g) with deionized water (1.5 parts, g). Zirconium acetate is added to the slurry as a solution, wherein 5 wt% of the Cu / Fe co-exchanged chabazite is already present in the slurry. The slurry is shear mixed at 2500 rpm for 30 minutes. Octanol (1-2 drops) may be added to defoam the stirred slurry.

[0126] Apply slurry to 13x13x3 in. 3 The core was dip coated, dried at 130°C for 4 minutes, and re-coated as needed to obtain a loading of 2.1 g / in 3 The support coating was applied and calcined at 450°C for 1 hour.

[0127] Example 2: Evaluation of Cu / Fe co-exchanged chabazite (CHA) catalyst as SCR catalyst for diesel NO reduction x

[0128] The nitrogen oxide selective catalytic reduction (SCR) efficiency of the fresh catalyst core was tested by feeding a feed gas mixture of 500 ppm NO, 500 ppm NH3, 10% O2 (by volume), 5% H2O (by volume), balance N2 into a steady-state reactor containing the Example 1 core.

[0129] For the catalytic experiments, the core with the carrier coating (size: 3 inches in length x 3 / 4 inches in width x 3 / 4 inches in height) was wrapped with a ceramic insulating mat and placed in an Inconel reactor tube heated by an electric furnace. O2 (from air), N2 and H2O as gases were preheated in a preheating furnace before entering the reactor. Reactive gases NO and NH3 were introduced between the preheating furnace and the reactor.

[0130] This reaction is at 80,000h -1 The reaction is carried out at a temperature in the range of 200-600° C. and at a space velocity of 1.5 %. The space velocity is defined as the value obtained by dividing the gas flow rate containing the entire reaction mixture by the geometric volume of the catalyst core. These conditions define the standard test for fresh catalyst.

[0131] The results are listed in Table 1. For the examples of the present invention, it was detected that with increasing iron oxide loading in the SCR composition, NO at 200°C x The change in conversion was minimal (e.g., Catalyst 2 vs. Catalyst 4). Interestingly, the NO x The conversion rate increases by about 10% with increasing iron oxide loading (e.g., commercial control material vs. Catalyst 4). Similarly, an increase in the total metal loading of the SRC composition and the conversion of NO at 600°C are also shown. x Increased conversion rate.

[0132] Table 1

[0133]

Claims

1. A catalyst composition comprising a zeolite having a chabazite (CHA) crystal structure exchanged with iron and copper ions.

2. The catalyst composition of claim 1, wherein the zeolite has a pore size of about 3-5 angstroms.

3. The catalyst composition of claim 1, wherein the CHA crystal structure is selected from the group consisting of aluminosilicate zeolites, borosilicates, gallosilicates, SAPOs, ALPOs, MeAPSOs, and MeAPOs.

4. The catalyst composition of claim 3, wherein the CHA crystal structure is an aluminosilicate zeolite having a silica to alumina ratio (SAR) of about 5 to 100.

5. The catalyst composition of claim 4, wherein the aluminosilicate zeolite has a silica to alumina ratio (SAR) of about 10 to 40.

6. The catalyst composition of claim 1, wherein the iron in the zeolite is present in an amount of about 0.01 to 6.0 weight percent of the final metal ion-exchanged zeolite, calculated as iron oxide (Fe2O3).

7. The catalyst composition of claim 1, wherein the iron in the zeolite is present in an amount of about 0.5-4.5 weight percent of the final metal ion-exchanged zeolite, calculated as iron oxide (Fe2O3).

8. The catalyst composition of claim 1, wherein the copper in the zeolite is present in an amount of about 0.01 to 6.0 weight percent of the final metal ion exchanged zeolite, calculated as copper oxide (CuO).

9. The catalyst composition of claim 1, wherein the copper in the zeolite is present in an amount of about 0.5 to 5 weight percent of the final metal ion exchanged zeolite, calculated as copper oxide (CuO).

10. The catalyst composition of claim 1, wherein the zeolite has a 2 / g of BET surface area.

11. The catalyst composition of claim 1 having a D 90 Particle size.

12. A method for preparing a CHA zeolite catalyst containing iron and copper, comprising: a. contacting chabazite (CHA) with a copper metal precursor and an iron metal precursor in a solution to form a solid CHA zeolite material containing iron and copper; b. drying the solid material to obtain a CHA zeolite catalyst containing iron and copper metal precursors; and c. Calcination of the CHA zeolite catalyst containing the catalyst containing iron and copper metal precursors to convert the catalyst into an active form.

13. The method of claim 12, wherein the copper metal precursor is copper acetate or copper nitrate salt.

14. The method of claim 12, wherein the iron metal precursor is iron (III) nitrate or iron (II) acetate salt.

15. The method of claim 12, wherein the chabazite (CHA) is Na-form chabazite and has been calcined prior to contacting with the copper metal precursor and the iron metal precursor.

16. The method of claim 12, further comprising heating the copper metal precursor and the iron metal precursor in solution with the CHA zeolite at an elevated temperature.

17. The method of claim 12, wherein the CHA zeolite catalyst containing the catalyst containing iron and copper metal precursors is calcined at a temperature of about 500-800°C.

18. The method of claim 12, wherein the solution is an aqueous solution.

19. A catalyst article comprising a catalyst substrate having a plurality of channels for gas flow, each channel having a wall surface adhered to a catalytic coating, the catalytic coating comprising the catalyst composition according to any one of claims 1 to 11.

20. The catalyst article of claim 19, wherein the catalyst substrate is a honeycomb substrate in the form of a wall flow filter substrate or a flow-through substrate.

21. The catalyst article of claim 19, wherein the catalytic coating has a concentration of at least about 1.0 g / in 3 of the load is present on the substrate.

22. A method for reducing NO in exhaust gas x The method comprises subjecting the exhaust gas to a catalyst at a level sufficient to reduce NO in the exhaust gas. x The method comprises contacting the catalyst with the catalyst at a temperature and time level, wherein the catalyst is a catalyst composition according to any one of claims 1 to 11.

23. The method of claim 22, wherein the NO in the exhaust gas x It is reduced to N2 at a temperature of about 200-600°C.

24. The method of claim 22, wherein the NO in the exhaust gas x The level decreases by at least 50% at 200°C.

25. The method of claim 22, wherein the NO in the exhaust gas x The level decreases by at least 70% at 600°C.

26. An emission treatment system for treating an exhaust stream, the emission treatment system comprising: i) an engine producing an exhaust stream; ii) The catalyst article of claim 19, which is located downstream of the engine and in fluid communication with the exhaust stream and is used to reduce NO in the exhaust stream. x to form a treated exhaust stream; and iii) an injector for adding a reducing agent to the exhaust stream to promote the conversion of NO to x Reduced to N2 and water.

27. The emission treatment system of claim 26, wherein the engine is a diesel engine.

28. The emission treatment system of claim 26, further comprising a diesel oxidation catalyst.

29. The emission treatment system of claim 26, wherein the reductant comprises ammonia or an ammonia precursor.

Citation Information

Patent Citations

  • Copper CHA zeolite catalysts

    US7601662B2

  • Process of direct copper exchange into Na+-form of chabazite molecular sieve, and catalysts, systems and methods

    US8293198B2

  • Process for the direct synthesis of Cu containing zeolites having CHA structure

    US8715618B2

  • Process for the preparation of zeolites having CHA structure

    US8883119B2

  • Copper CHA zeolite catalysts

    US9162218B2